2020
DOI: 10.1002/adpr.202000078
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Fiber‐Optic Intrinsic Electromagnetic Field Sensing

Abstract: Fiber‐optic sensing is resistant to electromagnetic interference; therefore, electromagnetic field sensing using fiber‐optic sensors is challenging. Herein, the first demonstration of fiber‐optic intrinsic electromagnetic field sensing based on modal interferometry with the highest reported sensitivity is presented (here, to be intrinsic means that the magnetic field interaction occurs only within the optical fiber, where there is no use of magnetic fluids or extrinsic structures). A fused polymer optical fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…[ 43 ] These effects result not only in the changes on refractive index, polarization, and so on, but also in the change of shape in magnetostrictive materials. Compared with the nonfused POF, the fused POF shows a 30 times higher magnetostriction, [ 44 ] which confirms the possibility of using the fused POFs in optical devices such as an intrinsic magnetic field sensor.…”
Section: New Perspectives and Applicationsmentioning
confidence: 79%
“…[ 43 ] These effects result not only in the changes on refractive index, polarization, and so on, but also in the change of shape in magnetostrictive materials. Compared with the nonfused POF, the fused POF shows a 30 times higher magnetostriction, [ 44 ] which confirms the possibility of using the fused POFs in optical devices such as an intrinsic magnetic field sensor.…”
Section: New Perspectives and Applicationsmentioning
confidence: 79%
“…Last year, 2020, Leal-Junior et al reported a fiber-optic intrinsic electromagnetic field sensor based on modal interferometry [ 69 ]. The sensor uses a short section of POF sandwiched between two SMFs.…”
Section: Mmi-based Fiber-optic Sensorsmentioning
confidence: 99%
“…In 1992, Hagen Renner et al [28] proposed that when single-mode optical fibers experience bending, the transverse field distribution ψ(x,y) in the optical waveguides can be expressed as the two-dimensional scalar equation, as shown in Equation (1).…”
Section: The Wavelength-bend Radius Relationmentioning
confidence: 99%
“…Optical fibers are part of everyday life, especially in communications, where they are used to convey information. Optical fibers have various advantages: low weight, small radius, high stability, high sensitivity, imperviousness to electromagnetic interference, and a high tolerance for harsh environmental conditions [ 1 , 2 ]. Due to their high sensitivities, optical fibers are widely applied in communications and have also displayed excellent performance in sensing and measurement applications [ 3 ].…”
Section: Introductionmentioning
confidence: 99%